Nitric oxide synthase and changes in oxidative stress levels in embryonic kidney observed in a rabbit model of intrauterine growth restriction. (2nd June 2016) - Figueroa, Horacio; Cifuentes, Jorge; Lozano, Mauricio; Alvarado, Cristobal; Cabezas, Claudia; Eixarch, Elisenda; Fernández, Ellio; Contreras, Luis; Illanes, Sebastian E.; Hernández‐Andrade, Edgar; Gratacós, Eduard; Irarrazabal, Carlos E.
Abstract: Objective: This work aimed to study the effect of uteroplacental circulation restriction on endothelial kidney damage in a fetal rabbit model. Methods: New Zealand rabbits were subjected to 40% to 50% of uteroplacental artery ligation at day 25 of pregnancy. After 5 days, surviving fetuses were harvested by cesarean section. The gene and protein expressions of selected enzymes associated with nitric oxide production and oxidative stress were analyzed in fetal kidney homogenates. Results: The placenta weight (6.06 ± 0.27, p  < 0.0319) and fetal body (19.90 ± 1.03, p  < 0.0001) were significantly reduced in the uteroplacental circulation restriction group. The kidneys from restricted fetuses presented a mild vascular congestion and glomerular capillary congestion, without inflammation or hypertrophy. We found endothelial nitric oxide synthase phosphorylation inhibition (0.23 ± 0.13, p  < 0.012) and arginase‐2 (0.29 ± 0.14, p  < 0.023) protein induction in fetal kidneys of the circulation restriction group. Finally, the kidneys from circulation‐restricted fetuses showed increased inducible nitric oxide synthase messenger RNA (mRNA) (2.68 ± 0.24, p  < 0.01) and reduced heme oxygenase‐1 mRNA (23 ± 1.3, p  < 0.003), with increased reactive oxygen species (1.69 ± 0.09, p  < 0.001) and nitrotyrosine protein (1.74 ± 0.28, p  < 0.003) levels, without changes in Nox mRNA. Conclusion: We describe significant deregulation of vascular activity and oxidative damage in kidneys of fetal rabbits that have been exposed to restriction of the uterine circulation. © 2016 John Wiley & Sons, Ltd. Abstract : What's Already Known About This Topic? Intrauterine growth restriction is defined as a failure of the fetus to reach its genetic growth potential. This condition is associated with increased risk of neonatal complications. What Does This Study Add? In this study, we found an important deregulation of vascular activity and oxidative stress damage in kidneys from intrauterine growth restriction fetuses. This condition might trigger genetic programming of fetal kidney, increasing the risk of developing adult diseases.